Achieving efficiency in autonomic network management of IP networks based on SDN management logic. (2018) - Lehocine, Madjed Bencheikh; Batouche, Mohamed
The layer-three redundancy in large companies' IP networks remains a major concern, aiming to increase, as much as possible, the availability ratio for the offered services to the customers. However, deploying the existing protocols requires in addition to providing backup links and physical equipment, the manual configuration which is time-consuming and error-prone. Autonomic router redundancy controller (ARRC) was the first autonomic solution whose objective was to deploy redundancy on existing networks. Yet, this solution was unable to handle redundancy in all network scenarios. In this paper, we propose a new approach extended ARRC (E-ARRC), inspired from software defined networking (SDN) management logic to address ARRC shortcomings and limitations. SDN represents a new vision for the future networks, aiming to reduce complexity and to ensure an efficient control of the network behaviour. Based on a global view of the network, SDN achieves business needs via a high-level specification of rules which are applied accordingly on the SDN capable nodes. The results of our approach, which is based on shared-networks reachability, illustrate a more granular level of redundancy, with a reliable exploitation of all the available resources.